Effect of Magnetic Field on Dilepton Production Rate in Relativistic Heavy Ion Collisions - Sethy, P. K.; Kumar, Y.; Singh, S. S. (Journal of Scientific Research, 2020)
It is believed that a transient strong magnetic field is generated in heavy-ion collision. The strength of this field perpendicular to the reaction plane and is estimated to be around eB=0.03GeV2 at RHIC and eB=0.3GeV2 at LHC. We study the effect of this magnetic field on dilepton yield using a modified quasi particle model. The results show a clear enhancement in dilepton yield and our result is in good agreement with the recently reported results.